Social Freedom, Emotional Maturity and Marital Adjustment of Working and Non-working Women - Sinha, Kumari Bharti (Journal of Advanced Research in English & Education; Vol 4 No 4 (2019): Journal of Advanced Research in English and Education, 2021)
This abstract deals with the social freedom, emotional maturity and marital adjustment in working and non-working women. First of all, these days, social freedom is seen in India. Women are becoming more and more mature with the advancement of time. In past, they are confined only to the household affairs. But, today they are working like their male counterparts in every walks of life. In such condition, the social freedom, emotional maturity and martial adjustment of working women and non-working women [house-wives] differ with one another. How to cite this article:  Sinha KB. Social Freedom, Emotional Maturity and Marital Adjustment of Working and Non-working Women. J Adv Res Eng & Edu 2019; 4(4): 15-19. DOI: https://doi.org/10.24321/2456.4370.201911